Fathering in the Chilean context: Wellbeing and father involvement pre and post the COVID-19 pandemic - Aldoney, Daniela (2022)
We examined father involvement in two groups of two-parent Chilean families with children aged from 2 to 7 years, one prior to the pandemic (N = 115) and the second during the pandemic (N = 103). We first presented a description of fathering in the Chilean context and then examined potential predictors of fathers’ cognitive and affective involvement. Data showed that during the pandemic fathers reported significantly higher levels of depressive symptoms compared to before the pandemic. However, levels of cognitive and affective involvement did not vary across studies. Parental stress predicted cognitive and affective involvement in pre-pandemic fathers. Number of children and educational level were related only to cognitive involvement. The implications of these findings for intervention and future research are discussed.